2012
DOI: 10.1002/ange.201201726
|View full text |Cite
|
Sign up to set email alerts
|

A “Smart” Catalyst: Sinter‐Resistant Supported Iridium Clusters Visualized with Electron Microscopy

Abstract: Wie Billardkugeln: Elektronenmikroskopische Untersuchungen an trägerfixierten Iridium‐Nanoclustern im atomaren Bereich zeigen, dass die Nanocluster Aggregate bilden, bis ein kritischer Durchmesser von ungefähr 1 nm erreicht wird, ohne danach weiter zu aggregieren (siehe Bild). Die Beobachtungen zeigen das Potenzial dieses Katalysators, der stabile Cluster bildet und eine nahezu optimale katalytische Aktivität hat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Artifacts such as these including migration of metal atoms or small clusters occur under these imaging conditions as reported elsewhere 29. 30…”
supporting
confidence: 58%
“…Artifacts such as these including migration of metal atoms or small clusters occur under these imaging conditions as reported elsewhere 29. 30…”
supporting
confidence: 58%
“…43 AC-STEM is capable of both high resolution and high sensitivity, but the electron doses conventionally used for atomic resolution imaging are high, approaching 10 6 e -/A 2 or more. These fluences can transfer significant energy to the adsorbed metals, such as iridium, leading to beam-induced sintering, 44 thereby complicating the interpretation of the native sizes of the metal-containing species. However, Ir-O-Ir species bound to α-Fe 2 O 3 surfaces (Figure 4) were shown to be stable under AC-STEM illumination for a minute or more.…”
Section: Experimental Structure Characterizationmentioning
confidence: 99%
“…For example, single-atom Ir supported on MgO was found to be intrinsically resistive to sintering, while Pt and Au supported on the same support material tended to sinter when they were treated in H 2 and the electron beam. [229] This phenomenon indicates the effect of the nature of metals themselves. Similarly, Campbell et al reported that Ag nanoparticles supported on reduced CeO 2 (111) have much higher stability than those supported on MgO (100), suggesting the effects of supports and metal-support interactions on the stability of SACs.…”
Section: Pyrolysis -Affordable In General Laboratoriesmentioning
confidence: 99%
“…The nature of metals, supports, and metal‐support interactions are the key factors affecting the stability of SACs. For example, single‐atom Ir supported on MgO was found to be intrinsically resistive to sintering, while Pt and Au supported on the same support material tended to sinter when they were treated in H 2 and the electron beam [229] . This phenomenon indicates the effect of the nature of metals themselves.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%